2010
DOI: 10.1096/fj.10-163022
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against the extra domain‐B of fibronectin as a novel tumor therapy

Abstract: Monoclonal antibody-based therapies have made an important contribution to current treatment strategies for cancer and autoimmune disease. However, the cost for these new drugs puts a significant strain on the health-care economy, resulting in limited availability for patients. Therapeutic vaccination, defined as induction of immunity against a disease-related self-molecule, is therefore an attractive alternative. To analyze the potential of such an approach, we have developed a vaccine against the extra domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…SEPT9 is homologous to septin-2, which is upregulated in cytoskeletal and immune function-related proteome profiles [54]. IFNGR2 is a four-domain fibronectin fragment, which plays a role in autoimmune diseases [55]. CSF3 is in PDB, and is related to immune system functions [56].…”
Section: Discussionmentioning
confidence: 99%
“…SEPT9 is homologous to septin-2, which is upregulated in cytoskeletal and immune function-related proteome profiles [54]. IFNGR2 is a four-domain fibronectin fragment, which plays a role in autoimmune diseases [55]. CSF3 is in PDB, and is related to immune system functions [56].…”
Section: Discussionmentioning
confidence: 99%
“…As important cancer markers in tumor ECM, EDA and EDB domains have been used as targets for cancer vaccination. A vaccine was developed against EDB-FN, which elicited production of anti-EDB antibodies and resulted in a 70% tumor volume reduction in T241 fibrosarcoma tumor model 146 . Vaccination against EDA showed that it could attenuate the progression of metastatic breast cancer 147 .…”
Section: Targeting Fibronectin In Cancer Therapymentioning
confidence: 99%
“…Applied together with a potent adjuvant cocktail, the immune system recognizes the modified self protein as non self leading to antibody production against the selected target protein. Such a therapeutic vaccine has been developed to target extradomain B of fibronectin (FN-EDB) or extradomain A of fibronectin (FN-EDA) and has shown antitumor activities in an in vivo fibrosarcoma tumor model 57 and in the MMTV-PyMT mouse model of breast cancer. 58 Vaccination of mice and rabbits against the C-domain of tenascin-C induced high serum titers of specific antibodies to the target 59 but its effect in preclinical cancer models is not yet reported.…”
Section: Anti-cancer Immunity and Cancer Immunotherapymentioning
confidence: 99%